Mixing regimes in a cluster of seven maar lakes in tropical monsoon Asia. Issue 1 (2nd January 2023) - Aguilar, Jaydan I.; Mendoza-Pascual, Milette U.; Padilla, Karol Sophia Agape R.; Papa, Rey Donne S.; Okuda, Noboru
ABSTRACT: The 7 maar lakes of San Pablo are a cluster of small volcanic lakes on Luzon Island, Philippines. These lakes, which are heavily utilized for aquaculture and ecotourism, usually experience fish kills that coincide with the northeast monsoon (NEM). This study explores limnophysical processes, particularly mixing regimes, in the lakes in relation to prevailing monsoons. We monitored monthly vertical and seasonal profiles of water temperature, salinity, conductivity, and dissolved oxygen from October 2016 to December 2018. Three types of mixing regimes were observed among the lakes, which have similar surface areas but different depths: polymixis in the shallowest; warm monomixis in lakes with intermediate depth; and meromixis in the deepest. A boundary between monomixis and meromixis was identified between 36 and 62 m depth. Monthly monitoring showed seasonal mixing occurred exclusively during the NEM (Nov–Apr). We also incorporated meteorological data into the model and performed multiple regression analysis for each lake to determine the best predictor: lake stability, as indicated by the Schmidt stability ( ST ). A between-lake comparison showed lake stability was strongly correlated with both air temperature and wind speed, suggesting these 2 meteorological variables are involved in establishing thermal stratification in the lakes during the southwest monsoon. This study provides insights for adaptive lake management and projections of climate impacts on these understudied tropical lake ecosystems in Southeast Asia.